90Y-ibritumumab tiuxetan (Zevalin) (Hematology Meeting Reports, 2009)
Introduction There is currently a range of different treatments available for the treatment of non-Hodgkin’s lymphoma (NHL). These include the more traditional therapies such as conventional cytotoxic agents, used alone, in combinations or as high-dose therapy with stem cell support; radiation therapy, which is recognized to be important as NHL is a highly radiosensitive tumour; and the newer biological therapies. Of the biological therapies, immunotherapy with the monoclonal antibody (mAb), rituximab, is perhaps the best established. A further development that combines the recognized benefits of radiotherapy and immunotherapy is the introduction of radiolabelled immunotherapy. This approach utilizes the specificity of an mAb to target the cytotoxic effects of radiotherapy towards antigen-positive tumour cells, thus delivering a high dose of radiation to the tumour and minimizing exposure of other organs and tissues to radiation. In addition, the ‘cross-fire’ activity of the radiation allows it to penetrate into surrounding tumour tissue, overcoming the problem of limited access in bulky or poorly vascularized tumours.